Echoes of consciences: systematic metamorphosis of gender discourse in the school space - Santana, Marcos (Nomadías, 2025)
This article reflects on the formation of gender identities in an institutionalized teaching space. He discovers that the performative discourse that subjects of early ages generate reproduce and naturalize both ideologies and conventional gender representations. I argue that the common of men in consequential ages occurs in a continuum of the reproduction of this cultural hegemonic image. However, women differ from this task, they insist on a principle of differentiation in that they construct an identity discourse outside of traditional symbolic manifestations. I argue that there are consciousnesses, masculinities and femininities, which transition to the establishment of a new gender order from the practical and discursive appropriation of the most common events in life.